MODERN ASPECTS OF DEVELOPMENT OF BUDGET POLICY OF KAZAKHSTAN - L.M. Sembiyeva,; A.O. Zhagyparova,; J.S. Raimbekov, (Academic Journal of Physical and Chemical Sciences, 2019)
The scientific article offers an analysis of the modern budget policy of Kazakhstan and the selection of the main directions of its development. The author assessed the effectiveness of the budget policy of the Republic of Kazakhstan in the field of income, which allowed us to distinguish 2 groups of problems of development of the budget policy of Kazakhstan - the problems of implementing the budget based on results and problems of budget planning and forecasting. To solve these problems, recommendations were made to address the problems of fiscal policy in Kazakhstan.